Universities’ Readiness in Designing Inter-University Shared Courses in Response to the Policy of Independent Learning - Independent Campus (ILIC) - Waluyo, Untung; Karta, I Wayan; Fahruddin, Fahruddin (Technium Sustainability, 2023)
The Ministry of Education and Culture of Indonesia launched the Policy of Independent Learning and Independent Campus (ILIC) through the Decree Number 3 of 2020. The emergence of this policy is a response to the issue of massively educated unemployment in the job market, both nationally and globally. The present study seeks to (1) describe the level of readiness of Indonesian universities in the island of Lombok in response to the ILIC policy related to the lecture exchange program among universities, (2) explore the hurdles faced by the local universities in preparing the exchange program and (3) investigate types of technical assistance needed by those universities to implement ILIC Policy effectively. This study employed a qualitative study approach with a multiple-case research design. as the basis for collecting, analyzing, and comparing data from various universities in Lombok Island. The selection of research participants was based on a purposive sampling technique. The main objective of employing this technique is to gather samples that are reasonably supposed to be representatives of the population. Results of the study show not all universities investigated were not ready to implement the ILIC policy due to lack of online learning facilities. For this reason, a big number of private campuses were found difficult to run inter-university exchange lectures. The study concludes there are two urgent needs that must be met by those campuses to run the ILIC policy successfully, i.e. (1) the provision of massive online learning facilities on campus and (2) collaboration among universities in carrying out non-lecture activities, such as practicum/ apprenticeship.